SIMULATION AND EXPERIMENTAL STUDY ON STRENGTH AND FATIGUE PERFORMANCE OF A SUV FRONT SUBFRAME (MT) - LIU KeMing; YUAN Xin; DAI YuSen (Jixie qiangdu)
In order to improve the reliability of the front subframe of a front drive SUV, the strength and fatigue characteristics of the subframe under different working conditions are analyzed by comprehensively using the finite element method, multi-body dynamics theory, strength analysis theory and fatigue analysis theory, and through the established three-dimensional model of the front subframe and the rigid flexible coupling model of multi-body dynamics. The strength and fatigue tests of the subframe are carried out. The simulation results show that the deformation of steering connection point is 2.924 mm and 3.411 mm respectively under straight driving and steering conditions, and the deformation of stabilizer bar and torsion arm is 3.383 mm and 2.695 mm respectively. The strength test results show that, in the straight driving and steering conditions, the deformation of the steering point is 3.263 mm and 3.622 mm respectively, which are 11.59% and 6.19% higher than the simulation results. The deformation of the connection point of the stabilizer bar and the connection point of the torsion arm are 3.538 mm and 2.957 mm respectively. The experimental results are 4.58% and 9.72% higher than the simulation results respectively. The results show that there is no obvious difference between the experimental results and the simulation results, and the deformation of the subframe at each point conforms to the design. The fatigue test results of the subframe show that there are no cracks and plastic deformation in the subframe after 800 thousand torsion arm fatigue tests, 400 thousand braking force fatigue tests and 800 thousand lateral force fatigue tests, indicating that the fatigue characteristics of the subframe meet the requirements.